Circular RNAs in osteosarcoma: An update of recent studies (Review) - Zeng, Le; Liu, Longzhou; Ni, Wen-Juan; Xie, Fuhua; Leng, Xiao-Min (International journal of oncology, 2023)
Osteosarcoma (OS) prevailing in children and adolescents mainly occurs at the metaphysis of long bones. As it is associated with a high invasive and metastatic ability, resistance to chemotherapy, and a low 5‑year survival rate, the diagnosis and treatment of OS post a global healthy issue. Over the past decades, RNA biology has shed new light onto the pathogenesis of OS. As a type of non‑coding RNAs, circular RNAs (circRNAs) have been found to play crucial roles in cellular activities. Recently, a large number of circRNAs have been identified in OS and some of them have been validated to be functional in OS. In the present review, abnormally expressed and different types of circRNAs in OS are summarized. Functional studies on circRNAs have revealed that circRNAs can regulate gene expression at different levels, such as gene transcription, precursor mRNA splicing, miRNA sponges and translation into proteins/peptides. Mechanistic analyses on circRNAs show that circRNAs can regulate JAK‑STAT3, NF‑κB, PI3K‑AKT, Wnt/β‑catenin signaling pathways during the occurrence and development of OS. Furthermore, the potential clinical applications of circRNAs are also emphasized. The present review focus on the current knowledge on the functions and mechanisms of circRNAs in the pathogenesis of OS, aiming to provide new insight into the OS diagnosis and treatment of OS.